Language Choice in Interracial Marriage Families: British-Indonesian Couples - NURMA PEBRIYATI (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
Language Choice in Interracial Marriage Families: British-Indonesian Couples Nurma Pebriyati S1 – Sastra Inggris Faculty of Arts and Language State University of Surabaya npebriyati@yahoo.com Slamet Setiawan English Literature Faculty of Arts and Languages State University of Surabaya slametsetia@yahoo.com Abstrak Pernikahan campuran antar ras telah menjadi sesuatu yang lazim saat ini. Dalam linguistik, pernikahan antar ras telah menyebabkan beberapa fenomena kebahasaan. Penelitian ini berfokus kepada pilihan bahasa dari keluarga campuran antar ras, terutama pasangan Indonesia-Inggris, yang tinggal di luar negeri. Tujuan dari penelitian ini adalah: untuk menggambarkan bahasa yang digunakan di rumah; untuk menggambarkan faktor yang mempengaruhi pilihan tersebut; dan untuk mengetahui seberapa besar pilihan bahasa dari keluarga tersebut mempengaruhi kelestarian dari bahasa daerah. Penelitian ini menggunakan metode kualitatif. Wawancara tulis digunakan untuk memperoleh data. Dari penelitian ini diperoleh informasi bahwa bahasa Inggris adalah bahasa yang dipilih oleh keluarga pernikahan campuran sebagai bahasa pertama dan yang paling banyak digunakan di lingkungan rumah. Ada beberapa faktor yang mempengaruhi keputusan tersebut, yaitu: lawan bicara, konteks sosial, dan fungsi. Keluarga-keluarga tersebut menggunakan bahasa yang berbeda ketika berkomunikasi dengan lawan berbicara yang berbeda dan dalam dan dalam situasi dan tempat yang berbeda. Fungsi dari suatu bahasa juga mempengaruhi para orangtua untuk memutuskan apakah akan mengajarkan bahasa tersebut kepada anak-anaknya atau tidak. Berdasarkan hasil penelitian, kebanyakan anak-anak dari pernikahan campuran tidak bisa berbicara bahasa daerah. Hal ini dapat menyebabkan bahasa daerah punah jika tidak diajarkan kepada generasi muda. Kata Kunci: pernikahan antar ras, pilihan bahasa, bahasa daerah, pelestarian bahasa. Abstract Interracial or mixed marriage has become a common thing nowadays. In linguistic field, interracial marriage has created some linguistic phenomena. This study focuses on the language choice in interracial family, particularly British-Indonesian couple, who live abroad. The purposes of this study are: to describe the language that the family choose in the home domain; to describe the factors behind their choices; and to find out how far the language choice influence the maintenance of ethnic language. This study uses qualitative approach. Written interview is chosen to collect the data. The findings of this study show that English is chosen by the families as their first language and frequently use in the home domain. There are some factors which influence the language choice they are participant, social context, and function. The families choose different language when communicate with different addressee and in different setting. The function of a language influences the parents whether to teach the language to their children or not. The findings also indicate that most of the children from mixed marriage family cannot speak ethnic language, it can caused the ethnic language to extinct if it is not being taught to the younger generation. Keywords: interracial marriage, language choice, ethnic language, language maintenance 1. INTRODUCTION Interracial marriage is a common thing nowadays. In Australia 28 percent of the population have multicultural ancestries (Khoo, 1991). Interracial marriage becomes an interesting subject for linguists to study, because interracial marriage has created some linguistic phenomena. Most of Indonesian people can speak at least two languages, their ethnic language and Indonesian as a national language. As a national language, Indonesian has more prestige than ethnic language, this is one of the reasons why younger generation now prefer to use Indonesian than ethnic language. Marriage between Indonesian and British people leave the couple with several choices of language that they and their children will use. There are some journals which also study about interracial marriage. One of the studies is Dumanig’s (2010) dissertation. Dumanig analyzes language choice in Filipino-Malaysian couples. In his study he found that there are several factors that influenced the couples’ language choice, they are ethnicity, first language, and gender. This study analyzes language choice in mixed marriage families, particularly in home domain, the factors which influence the choices, and the implication of the language choice on ethnic language maintenance. 2. LITERATURE REVIEW Most of the people in the world can speak more than one language (Brown and Attardo, 2000). Gupta (2010) stated that a child can acquire more than one language if adults around him/her frequently use more than one language. Children can learn a language if they think they need it, for example if their friends usually speak in X language and Y language, children will learn both of them. According to Holmes (2001) there are some factors which influence people to choose one language, they are: the participant, social context, function and topic of the discussion. It is important to consider who is the addressee. Different language may apply to different people, for example wife to husband, student to teacher, or boss to worker. Social context or setting, where and when the conversation happen, also can affecting the choices. Considering the purpose of the interaction is also important. Topic of the conversation can influence people to choose a certain language, because sometimes there are words or expression which cannot be translated correctly to other language, otherwise the “sense” of the words is different. For example, for university students in English literature major, it is easier to discuss the lectures in English. The relationship between the participants plays an important role in deciding the appropriate language or code (Holmes, 2001). People usually chooses a more formal language when they communicate with people who have higher status (e.g. parents, teachers, boss), and informal language when communicate with friends and people from a lower status (e.g. maid). According to Fishman (1976) language choice depends on the addressee, occasions, and topics. These factors are known as domains of language use. Somehow there are certain topics which can be explained or expressed better or more appropriate in one language than another. This appropriateness may be influenced by several factors. People may choose different language in a different domain. According to Edwards (1997) there are three important domains in people’s life, they are home, schools, and workplace. In the home domain (parents, grandparents, siblings, etc.) itself language choice may differ depending on the addressee. When speaking to parents, children tend to use more formal language or dialect and informal language is used to communicate with their siblings. While in schools and workplace, people usually use formal and national language The act of choosing one language among multilingual speakers inevitably force them to abandon the other languages. It can create another linguistic phenomena which is language shift and language death. Language death is when a language no longer has any speaker, while endangered language is language language is effectively dead when there is only one speaker left, with no number of the younger generation interested in learning it. Language maintenance is needed in order to protect ethnic languages. Ethnic identy is often accompanied by an increased interest in language maintenance ... This has led to the maintenance and revitalization of many endangered languages in parts of the world, and even to the revival of some extinct languages, e.g. among Australian Aborigines. (Janse, 2003). Language maintenance can be done by motivating the children to learn ethnic language, and educating them about language attitudes. A positive attitude is required in language maintenance (Clyne, 1991). According to Garafanga in Setiawan (2013) language proficiency is one of the factors which can determine the language choice. Language proficiency also influenced people’s attitude towards a particular language. Maintaining ethnic languages is essential because by maintaining this competence it will be easier to communicate with the family members and other people who belongs to the same ethnic language group. Having a similar ethnic language can create a closer bond between people. 3. METHOD This study uses qualitative approach, because this study is aimed to describe a certain phenomenon and the factors. The subject of this study is informants who give the data or information related to the study. The informants of this study are three families. The first family is British-Minangkabau couple with three children. The mother of this family comes from Padang, Indonesia, and the father is a British man. As a Minangkabau, the ethnic group who lives in Padang, she can speaks three languages, Minangkabau, Indonesian, and English. Now the family lives in Birmingham, United Kingdom. The second family is British-Sundanese couple, who have three children. The mother of this family is a Sundanese, and her husband is a British. The family now lives in Kuwait. The third family is British-Javanese couple with three children. The mother of this family is a Javanese, and her husband is British man. The family now lives in Birmingham, United Kingdom. Written interview is used to collect the data. The questions were sent to the families’ email and facebook accounts. In order to record the data, some tools are used in this study. They are facebook and email as the medium to sent the questions and answers, and then the written interview are captured using Screen Capturer software. According to Miles and Huberman (1994) there are three steps in analysing data, they are data reduction, data display, and conclusion and verification. Data reduction means reducing some data and carefully choose the data which are considered important and related with the study. In answering the questions, the informants sometimes add an information which is not related with the study. The data is displayed in the form of descriptive text. According to Miles and Huberman (1994) the data can be displayed in descriptive text and other forms such as graphic, matrix, chart, or table. The next step is giving a conclusion of the data which supported by some theories . 4. RESULTS AND DISCUSSION 4.1 Results 4.1.1 Language Choice in Interracial Marriage Families In the home domain, the families choose different language when communicating with different addressee. In the first family (next they will be called as F1), the mother usually mixes English with Indonesian language when speaking to her children. She wanted her children to be able to speak Indonesian language as good as their ability in English. Now the children can speak Indonesian fluently. Mother of the second family (next they will be called as F2) also use English and Indonesian to communicate with her children. The family had lived in Indonesia for two years. It helped the children to improve their knowledge and proficiency in Indonesian, and now the children are very fluent in Indonesian. (01) Saya mulai berbicara sedikit demi sedikit dengan bahasa Indonesia dengan anak-anak.... kami pindah ke Indonesia (hanya 2 tahun saja), buat kami itu kesempatan yang bagus karena anak-anak bisa lebih mengenal/ belajar bahasa Indonesia lebih jauh lagi (I started to talk in Indonesian slowly to the children.... we moved to Indonesia (only for 2 years), for us that was good because the children can learn Indonesian language further). Mother of the third family (next they will be called as F3) only uses English when communicating with her children. She does not have an intention to teach her children Indonesian or Javanese. The children only know few Indonesian words, which they learnt from their relatives in Indonesia. (02) Sedikit, mereka belajar dari saudara dan sepupu mereka. (A little, they learnt it from their cousins and nephews) The father of the three families use English when communicating with their children. Father of F1 and F3 cannot speak Indonesian, so the only language that they can use to communicate with their children is English. While the father of F2 can speak Indonesian fluently. Despite the fact that both father and children of F2 can speak Indonesian, they only use English when talking to each other. In order to communicate with their siblings, the children of the three families choose English. Eventhough the children of F1 and F2 can speak Indonesian, but they feel more comfortable speaking whith their siblings in English (see data 03). (03) Mereka menggunakan bahasa Inggris, karena mereka lebih nyaman menggunakan bahasa Inggris (They use English, because they feel more convenience using English) The three families choose English when communicating with their spouses. Husbands of the F1 and F3 cannot speak Indonesian, so the only way they can communicate with their wives is using English. While the F2, they often switch from English to Indonesian, as stated by his wife in (04). (04) Bahasa Inggris dan bahasa Indonesia ((when communicating with her husband) English and Indonesian) At F1 and F3 houses there are only their families, while F2 also lives with a maid who comes from Sri Lanka. They use English to communicate with their maid eventhough they live in Kuwait , since the F2 cannot speak Arabic nor Sinhala (Official language of Sri Lanka) while the maid did not understand Indonesian language. (05) Assisten rumah tangga kami berasal dari Srilanka. Berbicara menggunakan bahasa Inggris (Our maid comes from Srilanka, she speaks English 4.1.2 Factors That Influence The Language Choice There are three factors which influence the families’ language choice, they are: participants, social context or setting, and function. The families choose different language depending on the addressee. Mother of F2 uses different language when communicating with her husband and her maid. She uses English and Indonesian to communicate with her husband, and use English only when communicating with her maid. The setting also can influence people to choose a certain language. Bilingual speaker usually chooses different language in different setting. The children of F1 use English at school, but when they visiting their grandparents in Indonesia, they will use Indonesian. The third factor which can influence the language choice is function. Each interaction has a purpose which can determine what language that they are going to choose. The F1 and F3 who live in England, and F2 who was lived in England for eight years, choose English as a first language for their children because of its function as a community language. In England, majority of the people speak English. (06) Bahasa Inggris karena lingkungan sekitarnya mereka pakai bahasa Inggris..... (We use English because people around us use English) The function of a language is the factor why F1 and F2 teach Indonesian and ethnic language to their children. they found that Indonesian and ethnic language still bring benefit in their lives, one of the benefit is they can communicate with their families in Indonesia. While the F3 found that they do not need to learn Indonesian or Javanese, because without those languages they still can interact with their family in Indonesia using English 4.1.3 Language Maintenance Concerning with ethnic language, all families admit that their children have lack of knowledge about their mother’s native language. F1 and F2 still expecting that their children can speak Indonesian and ethnic languages fluently. Children of the first and second family already acquire a good Indonesian language. Both F1 and F2 show positive attitude towards Indonesian and their ethnic languages, it is proved by their actions and willingness to teach the languages to their children. (07) Ya, saya ingin anak-anak bisa berbicara bahasa sunda. (Yes, I want my children to be able to speak Sundanese) The interesting fact is that husband of the second family, not only can speak Indonesian fluently, he also has a strong interest in learning Sundanese, her wife’s ethnic language. (08) Suami saya dapat berbicara bahasa indonesia fluently. Bisa berbicara bahasa sunda sedikit. (My husband can speakIndonesian fluetly, and a little bit of Sundanese) Different from F1 and F2, F3 when being asked about whether they will taught their children Indonesian or Javanese or not, they show lack of interest on that idea. As a result her children have lack of knowledge both on Indonesian and Javanese as her ethnic language. From the data above, it can be seen that parents play an important role in language maintenance. Parents who have positive language attitude towards their ethnic language tend to teach their children ethnic language despite they live in other country. Meanwhile parents who have negative attitude unlikely to teach their children ethnic language. Other factor is function. When a person finds that he/she still need a certain language, he/she will maintain it. F2 found that she still need Indonesian and Sundanese in order to communicate with her family in Indonesia. Therefore, she teaches her children Indonesian, and still maintaining her national and ethnic language eventhough she lives in other country. F1 and F2 can maintain the use of Indonesian language by teaching their children Indonesian. While great effort is still needed in order to introduce the children to ethnic languages. In F3 Indonesian and Javanese language are not taught to their children. It is due to the fact that most of their family, even those who live in Indonesia, can speak English. (09) Hampir semua keluarga saya bisa bahasa Inggris karena bapak saya punya kursus bahasa Inggris. (Almost all of my family can speak English because my father has an English course.) The Javanese proficiency of F3 mother is also the factor which influenced the family’s choice to not teaching Javanese to the children. Eventhough the mother is a Javanese, but she cannot speak polite Javanese of krama (see data 10). The lack of knowledge in Javanese krama makes the mother reluctant to teach her children Javanese, and grow a negative attitude towards Javanese. (10) Saya selalu berbahasa Jawa kasar dengan keluarga. (I always use Javanese ngoko to my family) F3 cannot maintain the use of Indonesian and Javanese in their family because they did not find the benefit of the languages for their family. The mother’s lack of proficiency in Javanese also contribute to the negative attitude towards Javanese. 4.2 Discussion 4.2.1 Language Choice in Interracial Marriage Families Based on the data, interracial marriage couples choose English as the first language in their family, and children of two from three families can speak Indonesian. Children of interracial couples can be multilingual speakers naturally. They acquire languages from both their parents. Children of the families now can speak two languages, English and Indonesia. They acquire English naturally as their first language, because they live in English-speaking country and both their parents speak English, as shown in data (11). While Indonesian being taught to them by their mother and also their relatives when visiting Indonesia. Unlike English as their first language that they use regularly, they only use Indonesian when they speak to their mother and relatives in Indonesia. (11) Saya mulai berbicara sedikit demi sedikit dengan bahasa Indonesia dengan anak-anak. (Slowly I start to speak In Indonesian with my children) Gupta (2010) stated that a child can acquire more than one language if adults around him/her frequently use more than one language. Children can learn a language if they think they need it, for example if their friends usually speaks in X language and Y language, children will learn both of them. 4.2.2 Factors That Influence The Language Choice English is the language that the couples choose as first language in their families. There are three factors which influenced them, they are participants, settings and function. The linguistic choices depend on the addressee, occasions, and topics (Fishman, 1976). These factors are known as domains of language use. Holmes (2001) stated some factors which influence people to choose one language are: the participant, social context, and function. It is important to consider who is the addressee. Different language may apply to different people. Social context, where and when the conversation happen, also can affecting the choices. Holmes (2001) theory is in line with this study where the families use different language when communicate with different addressee. Children of the F1 mixing English and Indonesian to their mother, and they only use English when speaking to their father. Children when speaking to their father (12) Bahasa Inggris karena itu yang bisa dimengerti kedua belah pihak (English, it is the only language that can be understood by all of them) Children when speaking to their mother (13) Bahasa Inggris dan bahasa Indonesia (English and Indonesian) Social context or setting also plays an important role in determining language choice (Holmes, 2001). In this study found that the F1 and F2 choose different language in a different setting. The two families choose English when they communicate with their spouses, and when they go to their hometown in Indonesia they use Indonesian and their ethnic language. The other factor is function. The F1 and F2 found that they still need Indonesian and ethnic language in order to communicate with their families who still live in Indonesia. The children also can feel the benefit of learning their mothers’ native language when they meet their Indonesian families. Gupta (2010) stated that a child can acquire more than one language if adults around him/her frequently use more than one language. Children can learn a language if they think they need it. Language choice can be influenced by several things, each person may have different reason. In this study found that the factors that encourage the informants to make a linguistic choice are: participant, social context and function. 4.2.3 Language Mintenance Indonesian and ethnic language, in certain occasion, are still used by the first and seccond families. Eventhough they do not use it regularly. The willingness of the mothers to teach their children about Indonesian and ethnic language can help the language preservation or maintenance. Friends and family of first and second family still use Indonesian to talk to the children. This is in line with Fillmore (2000) theory that community can help ethnic languages and cultures to survive. By using Indonesian language to the children, they have helped the children to learn the language. The children is motivated to keep using Indonesian since they see their parents, as a role model, are still using Indonesian despite living abroad. Parents participation is very crucial, because they are the only one who can teach their children to appreciate the heritage of the ancestor and grow a positive language attitude in them. A positive attitude is required in language maintenance (Clyne, 1991). A positive attitude will encourage someone to maintain the language by introduce it to the next generation. This effort needs support from both mother and father. F1 and F2 show positive attitude towards Indonesian and ethnic languages. From the data above can be seen that husband who can appreciate his wife ethnic language, can help the mother to teach their children. Children also can look up to their father (F2), who is a British man, but shows a strong interest in ethnic language. Language proficiency also can influence the language attitude (Garafanga in Setiawan, 2013). Parents who have low proficiency will tend to have a negative attituce towards the language. It can be seen from the F3 who has low proficiency in Javanese krama and does not have intention to teach the language to their children. Language maintenance is important for the next generation. Maintaining this language helps younger generation to value their culture and sacred heritage from their ancestors, which contributes to a positive self-concept. 5. CONCLUSIONS AND SUGGESTIONS 5.1 Conclusions Based on the research, interracial couples choose English as first language for their children. English is language that most frequently use by the families. In the home domain English is used to communicate with all of the family members; parents, spouse, siblings, and maid. There are some factors that influence their choises. One of the reasons is participant. The families choose different language when communicate with different addressee. Social context and function are also the factors in choosing language. Setting of the conversation can influence the families to choose a certain language. The families consider the function of a language when choosing language(s) that they want their children to master. The F3 found that even without Indonesian language they still can communicate with their Indonesian families using English, therefore they did not teach their children Indonesian. Despite living outside Indonesia, the F1 and F2 still use and teach their children Indonesian and ethnic language. It is a positive sign for the language maintenance, because still there will be younger generation who will learn ethnic language. Younger generation have a big role in language maintenance. If all mixed marriage couples reluctant to teach ethnic language to their children, soon ethnic language will dissapeared, since there is no more people who can speak and understand the language. 5.2 Suggestion This study is still far from “perfect”, advice and suggestion are needed in order to make this study better. As for the next researchers, using the combination of qualitative and quantitative method will increase the accuracy of a study. Combining interview and observation can give a researcher wider data. REFERENCES Brown, S., & Attardo, S. (2000). Understanding Language Structure, Interaction and Variation: An Introduction to Applied Linguistic and Sociolinguistics for non Specialists. USA: The University of Michigan Press. Clyne, M. (1991). COMMUNITY LANGUAGES: THE AUSTRALIAN EXPERIENCE (1 ed.): Cambridge University Press. Dumanig, F. P. (2010). Language Choice in Interracial Marriages: The Case of Filipino-Malaysian Couples. (Dissertation), Florida. Edwards, J. (1997). Language Minorities and Language Maintenance. Annual Review of Applied Linguistics 17. 30-42. Fishman, J. A. (1976). Bilingual education: an international sociological perspective. Rowley, Mass.: Newbury House Gupta, A. F. (2010). Bilingual and Multilingual Children: Another Perspective. Retrieved from Ask A Linguist FAQ website: http://linguistlist.org/ask‐ling/biling2.html Holmes, J. (2001). An Introduction to Sociolinguistics. United Kingdom: Longman. Janse, M. (2003). Language Death and Language Maintenance: Theoretical, Practical and Descriptive Approaches (Current Issues in Linguistic Theory). Amsterdam: John Benjamins Pub Co. Khoo, S E (1991). ‘Consistency of ancestry reporting between parents and children in the 1986 census’, Journal of the Australian Population Association 8 (2): 129-139. Setiawan, S. (2013). Children's Language in a Bilingual Community in East Java. Germany: Scholars' Press.